Evaluation of left atrial and ventricular remodeling in atrial fibrillation subtype by using speckle tracking echocardiography - Lu, Shirui; Liu, Hongyun; Sun, Jie; Zhang, Jun; Li, Li; Tang, Qiaoying; Liu, Yani; Deng, Youbin (Frontiers in Cardiovascular Medicine, 2023)
Background: Atrial fibrillation (AF) is associated with cardiac structural and functional remodeling. We investigated left atrial (LA) and left ventricular (LV) changes in AF subtype by using twodimensional echocardiography strain techniques.Methods: Study population consisted of 463 patients with AF, including 284 patients with paroxysmal AF (PAF) and 179 patients with persistent AF (PerAF), and 102 sinus rhythm controls. Speckle tracking automatic functional imaging software was used to perform strain analysis.Results: Patients with AF had dilated LA maximum and minimum volume, decreased LA reservoir strain, lower LV ejection fraction (LVEF) and impaired global longitudinal strain (GLS) as compared to sinus rhythm controls. LA maximum and minimum volume were larger, LA reservoir strain (PAF vs. PerAF, 28 (21,33) vs. 19 (14, 28) %, P < 0.05), LVEF and absolute value of GLS (PAF vs. PerAF, -16.9 ± 3.3 vs. -14.1 ± 3.5 %) were lower in PerAF than PAF. Patients with AF regardless of LA enlargement had decreased LA reservoir strain, lower LVEF and absolute value of GLS than sinus rhythm controls.Compared with normal sinus rhythm, patients with AF had dilated LA volume and impaired LA function, which were further worsened in patients with PerAF than PAF. LA functional impairment occurred before LA enlargement. Left atrioventricular remodeling happened across different stages of AF development.